Review Of M-Government in Developing Countries: The Case of Egypt - Elbatanouny, Sherif; Dafoulas, Georgios; Saleeb, Noha (Journal of Government and Civil Society, 2023)
In response to advances in Information and communication technologies (ICT) and the need for more effective and efficient administration, governments in a number of countries have devised m-government initiatives to increase the amount of information and online services accessible to citizens, government agencies, and businesses. The utilization of information technology to bridge the gap that exists between administrative entities and establish a virtual government is at the heart of the concept of mobile government (m-government). Yet, governments are being forced to prepare for the transition from e-government to m-government due to the increasing mobility of citizens in industrial economies and the widespread adoption of internet-enabled mobile phones and personal digital assistants (PDAs) are examples of gadgets that can access the internet wirelessly. As a developing country, Egypt started investing in communication and IT infrastructure in 1985, while it was still in economic transition and development. Egypt is currently struggling to overcome a variety of challenges that have prevented it from fully implementing m-government applications. This is mostly attributable to the typical challenges or obstacles that might restrict the development of any government. In contrast to other nations across the world, Egypt is still in the early stages of m-government development, which is reviewed in this paper. Challenges of the m-government in Egypt include a discussion of the services for mobile applications provided by the government that are already being utilized. Additionally, suggestions are made for how Egyptian m-government could evolve moving forward, and the advantages of using various m-government services for citizens are outlined.Menanggapi kemajuan teknologi informasi dan komunikasi (TIK) dan kebutuhan akan administrasi yang lebih efektif dan efisien, pemerintah di sejumlah negara telah merancang inisiatif m-pemerintah untuk meningkatkan jumlah informasi dan layanan online yang dapat diakses oleh warga negara, lembaga pemerintah, dan lembaga pemerintah. dan bisnis. Pemanfaatan teknologi informasi untuk menjembatani kesenjangan yang ada antara entitas administratif dan membentuk pemerintahan virtual merupakan inti dari konsep mobile Government (m-Government). Namun, pemerintah terpaksa mempersiapkan transisi dari e-Government ke m-Government karena meningkatnya mobilitas warga negara di negara-negara industri dan meluasnya penggunaan telepon seluler yang dilengkapi internet dan Personal Digital Assistant (PDA) adalah contoh dari gadget. yang dapat mengakses internet secara nirkabel. Sebagai negara berkembang, Mesir mulai berinvestasi dalam infrastruktur komunikasi dan TI pada tahun 1985, ketika Mesir masih dalam masa transisi dan pembangunan ekonomi. Mesir saat ini sedang berjuang untuk mengatasi berbagai tantangan yang menghambat penerapan aplikasi m-Government secara penuh. Hal ini sebagian besar disebabkan oleh tantangan atau hambatan yang mungkin menghambat perkembangan pemerintahan mana pun. Berbeda dengan negara-negara lain di dunia, Mesir masih berada pada tahap awal pengembangan m-Government, yang akan diulas dalam makalah ini. Tantangan m-goverment di Mesir mencakup diskusi mengenai layanan aplikasi seluler yang disediakan oleh pemerintah yang sudah dimanfaatkan. Selain itu, saran-saran juga diberikan mengenai bagaimana m-Government Mesir dapat berkembang ke depan, dan keuntungan dari penggunaan berbagai layanan m-Government bagi masyarakat juga diuraikan.